GC-MS and ADMET Profiling of Bruguiera gymnorrhiza Mangrove Leaf Extract Origin Sulawesi with Antioxidant Properties - Wendy Alexander Tanod; Didit Kustantio Dewanto; Eko Cahyono; Frets Jonas Rieuwpassa; Novalina Maya Sari Ansar; Yana Sambeka; Frans Gruber Ijong; Jefri Anthonius Mandeno; Obyn Imhart Pumpente; Meilya Suzan Triyastuti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Mangrove plants, particularly Bruguiera gymnorrhiza, are recognized as sources of bioactive compounds. This study analyzed the chemical profiles, safety, and antioxidant activity of B. gymnorrhiza leaf extract origin Sulawesi, a biodiversity-rich Wallacean region. Research on B. gymnorrhiza leaves from Sulawesi remains scarce. GC-MS analysis identified inositol, fatty acid, ester, and terpenoid derivatives as major chemical profiles related to stress tolerance and remedial properties. ADMET predictions showed good intestinal absorption but suggested potential hepatotoxicity at high doses. Brine shrimp lethality tests revealed low acute toxicity with an LD₅₀ of 873.381 µg/mL, supporting in silico findings. The extract exhibited strong antioxidant activity (IC₅₀ 49.78 µg/mL), comparable to Vitamin E, and higher than reports from other regions. These results indicate that Sulawesi mangroves store valuable chemical compounds and serve as environmental health indicators. Combining chemical profiling, computational prediction, and experimental validation highlights their pharmaceutical potential while emphasizing the need for careful dose optimization and ecological monitoring. This study reinforces the importance of conserving Wallacean biodiversity and offers a foundation for safe, natural antioxidant commercialization. Future work should assess in vivo effectiveness, long-term toxicity, and the ecological impacts of pollutant immobilization in mangrove ecosystems.